2019
DOI: 10.1088/1742-6596/1317/1/012106
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of uncaria gambir roxb on T47D breast cancer cells

Abstract: Breast cancer was the second most common cancer that causes death in women worldwide. One ingredients of herbal plants as an alternative therapy in the community, was gambir leaves. This research was conducted to examine the anticancer activity of Uncaria gambir Roxb on T47D breast cancer cells in vitro. Six levels of concentration U. gambir (31.25 mg/ml up to 1000 mg/ml) was included on the 96 microplate well which had been filled with breast cancer cells, the positive control was doxorubicin (with concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…Gambir, which is rich in flavonoid secondary metabolite compounds, especially catechins, has antioxidant activity that can capture free radicals [ 93 ], having great potential as an anticancer. Syarifah et al [ 14 ] investigated the anticancer activity of gambir on T47D breast cancer cells in vitro. The results showed that gambir inhibited breast cancer cell growth, although this property was still weaker than doxorubicin (DOX) as a positive control.…”
Section: Uncaria Gambir Roxb Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambir, which is rich in flavonoid secondary metabolite compounds, especially catechins, has antioxidant activity that can capture free radicals [ 93 ], having great potential as an anticancer. Syarifah et al [ 14 ] investigated the anticancer activity of gambir on T47D breast cancer cells in vitro. The results showed that gambir inhibited breast cancer cell growth, although this property was still weaker than doxorubicin (DOX) as a positive control.…”
Section: Uncaria Gambir Roxb Usesmentioning
confidence: 99%
“…With the continuous improvements in medicinal plant research methods, increasing numbers of compounds including alkaloids, flavonoids, and tannins have been discovered from gambir. Modern studies have shown that gambir has pharmacological activities such as anticancer [ 14 ], enzyme inhibitory [ 15 ], and hypoglycemic [ 16 ] activity due to flavonoid compounds [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Semua senyawa tersebut diklaim mampu mengobati berbagai penyakit degeneratif layaknya diabetes, kanker, tumor, dan lain-lain. Hal ini diperkuat dengan penelitian yang telah di lakukan (Syarifah et al 2019) yang menyatakan bahwa akar bajakah tampala dapat mengobati penyakit kanker. Ayuchecaria et al (2020) menyatakan bahwa ekstrak batang bajakah tampala rata-rata mengandung kadar fenolik sebesar 12,33mg GAE/g.…”
Section: A Karakteristik Tanaman Akar Bajakahunclassified
“…Terdapat 200 jenis bajakah di Indonesia, khususnya di Kalimantan. Meskipun terdapat ratusan jenis bajakah di Indonesia, namun belum ada penelitian ilmiah terkait aktivitas sitotoksisitas dari bajakah (Åkesson et al, 2003;Batiha et al, 2020;Cheng et al, 2007;Stephenson, 1931;Syarifah et al, 2019). Oleh karena itu, perlu adanya usaha…”
Section: Pendahuluanunclassified